Giuseppe e i suoi fratelli: un progetto non realizzato di Luchino Visconti (Altre Modernità, 2011)
In 1963, Luchino Visconti signed a contract with producer Dino De Laurentiis to direct a film inspired by the biblical story of Giuseppe and his brothers. Giuseppe e i suoi fratelli was meant to be a part of an Italian colossal along with several other episodes to be directed by renowned artists such as Orson Welles and Robert Bresson. Analysing letters and several versions of the screenplay never studied before, this essay trace a thorough story of this project and explains the reasons of its failure. Even if Visconti accepted De Laurentiis’s offer only to be sure that the producer would fund his adaptation of Camus’s The Stranger, Giuseppe e i suoi fratelli interested him because it gave him a second chance to work on the monumental version of Giuseppe’s story written by Thomas Mann. A few years before, Visconti had already written a treatment for Rocco e i suoi fratelli under the influence of this beloved novel, but he had abandoned every reference to it in the following development. Unfortunately, Christopher Fry, an American playwright and screenwriter also involved in the biblical project, failed to understand Visconti’s predilection for the novel and rejected any influence of the German writer. Despite Visconti’s efforts to find a compromise, the director’s conception of the story (and of cinema as well) was too far from Fry’s one, as the three different screenplays written by them for the project show in an unmistakable way, and the director was dismissed by the producer without any notification.
Keywords: Bibbia; Giuseppe e i suoi fratelli; Luchino Visconti; Thomas Mann; Dino De Laurentiis; Christopher Fry